2014
DOI: 10.1007/s11552-014-9618-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Response Rates between Mail, E-mail, and Telephone Follow-Up in Hand Surgery Research

Abstract: Prognostic I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 12 publications
4
38
0
Order By: Relevance
“…Responses to online surveys from CARRA and PeDRA members were about 24 and 27%, respectively, which can be considered a low response rate. We found that survey responses pertaining to this topic are lower compared to earlier surveys from CARRA [13, 14, 16, 17], however, it should be noted that our present survey response rates are comparable to current reported online survey response rates [37, 38]. The surveys were sent to the full CARRA and PeDRA membership, and not a specific subset of JDM experts, but it is reasonable to postulate that clinicians with more exposure and expertise to JDM were more likely to respond to the surveys.…”
Section: Discussionsupporting
confidence: 61%
“…Responses to online surveys from CARRA and PeDRA members were about 24 and 27%, respectively, which can be considered a low response rate. We found that survey responses pertaining to this topic are lower compared to earlier surveys from CARRA [13, 14, 16, 17], however, it should be noted that our present survey response rates are comparable to current reported online survey response rates [37, 38]. The surveys were sent to the full CARRA and PeDRA membership, and not a specific subset of JDM experts, but it is reasonable to postulate that clinicians with more exposure and expertise to JDM were more likely to respond to the surveys.…”
Section: Discussionsupporting
confidence: 61%
“…This may have occurred because we made contact by mail instead of phone. Literature confirms that response rates by phone are higher than by mail or e-mail (Nota et al, 2014). Moreover, the adolescents had to ask for their parent's consent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the adolescents had to ask for their parent's consent. Both younger age and higher pain intensity seem to be associated with a lack of response (Nota et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nota et al reported similar response rates for electronic and paper questionnaires in a cohort of patients presenting to a hand and upper extremity department; interestingly, they found telephone contact to yield higher response rates [17]. By contrast, Palmen et al found a far greater response rate for paper questionnaires sent to a cohort of patients following surgery for hallux valgus [6].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%